Solidarity and sweat equity: for reciprocal food justice research - Sbicca, Joshua, author; Thomas A. Lyson Center for Civic Agriculture and Food Systems, publisher (Colorado State University. Libraries, 2015)
Researchers committed to food justice often enter communities and nonprofits with a desire to help. They often think there is a scarcity, such as food, that they want to understand and help to increase. At the same time, research obligations may lead to extracting "findings" without advancing food justice. Such actions may unintentionally work against food justice, especially the goal of dismantling structural inequalities and advancing social equity. This commentary chronicles the ongoing and incomplete process by which I have carried out food justice research and worked toward food justice. In short, reciprocal research requires working with, not for, organizations and communities. This entails ongoing acts of solidarity. One way to express this is through flexibility with research goals in order to tailor all or parts of one’s project to answer questions that increase understanding of how to challenge structural inequalities and advance social equity. Relatedly, openness to how food justice activists and organizations confront the food movement and society more broadly to address whiteness, privilege, racial inequality, and notions of diversity can enrich critical social science. Of equal importance is sweat equity. Most food justice activists and organizations have few resources and cannot serve the whims of researchers. Therefore, providing labor is an important allied act. This increases the researchers' empathy with activists, organizations, and communities, and creates opportunities to build trust and dissolve social boundaries. To enter into a situation that deepens our knowledge of the food justice movement and advances food justice requires solidarity and sweat equity.
Keywords: allyship; anti-oppression; anti-racism; food studies; food movement; food justice; methodology; public sociology; solidarity; sweat equity